Estimasi Tingkat Pengurusan e-KTP Menggunakan Metode Brown’s-DES Berbasis Web (Studi Kasus : Disduk Capil Kab. Sorong): Estimasi Tingkat Pengurusan e-KTP Menggunakan Metode Brown’s-DES Berbasis Web (Studi Kasus : Disduk Capil Kab. Sorong) - Soleha Rahayu Muklis Hayu; Rendra Soekarta; Muhammad Rizki Setyawan (Universitas Muhammadiyah Sorong, 2022)
Electronic Identity Card (e-KTP) is the official identity of the resident as proof issued by implementing agencies that are valid throughout the territory of the Unitary State of the Republic of Indonesia. Electronic Identity Card is one of the population documents that must be owned by every citizen in order to create good population administration. One of the obstacles to e-KTP ownership that makes people reluctant to take care of the population document is the delay in printing the e-KTP, such as a shortage of tools and materials used for printing e-KTP, such as running out of blanks, ribbons, films and damaged printers, so a system is needed. which can assist in predicting the estimated level of management of the e-KTP. Creation of a system that can predict the estimated level of web-based e-KTP management that can assist agencies in supporting work in terms of printing e-KTP. The design of a forecasting system for estimating the level of e-KTP management at the Sorong Regency Population and Civil Registration Service uses flowcharts and use cases. System development uses a prototype model with the Brown's Double Exponential Smoothing method. The results of this study are an estimation forecasting system that is expected to overcome delays in printing e-KTP at the Sorong Regency Population and Civil Registration Service.